2006
DOI: 10.1093/her/cyl044
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviour and academic achievement in Icelandic school children

Abstract: Interest in the relationship between health behaviours and academic achievement has recently intensified in the face of an epidemic of childhood and adolescent obesity and converging school reforms in the United States and other nations with advanced economies. Epidemiologic research has demonstrated that poor diet and lack of adequate physical activity place children at risk for being overweight and obese and thus influence future health status. Additional research has also shown that children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
175
5
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(205 citation statements)
references
References 30 publications
9
175
5
16
Order By: Relevance
“…Recent population studies from children and youth in Iceland lend support to this hypothesis as cross-sectional associations between higher BMI, psychological maladjustment and lower academic competencies, as displayed by academic performance, were observed. 17,29 Also supporting the hypothesis are results from studies in general samples that consistently show psychological adjustment to be an important predicting factor for academic competencies and performance, as well as for academic attainment. 30,31 Education and academic attainment is highly correlated with income and occupation and it is one of the most important predictors of health.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Recent population studies from children and youth in Iceland lend support to this hypothesis as cross-sectional associations between higher BMI, psychological maladjustment and lower academic competencies, as displayed by academic performance, were observed. 17,29 Also supporting the hypothesis are results from studies in general samples that consistently show psychological adjustment to be an important predicting factor for academic competencies and performance, as well as for academic attainment. 30,31 Education and academic attainment is highly correlated with income and occupation and it is one of the most important predictors of health.…”
Section: Introductionmentioning
confidence: 68%
“…However, a higher degree of overweight has not been associated with an increased risk of psychological maladjustment in clinical samples of obese children, 2,9-11 although this association has been commonly observed among community-based samples. [17][18][19] Few studies have been published about the moderators and mediators of the association between childhood obesity and academic competencies, but suggested factors include parental education and SES, child's gender, school absenteeism, 6,7,17,20 diet and physical activity, 17 psychological adjustment 17 and most recently weight-based stigma, teasing and social rejection. 8 Among children in general, approximately 17-30% report experiencing teasing and social rejection.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the correlation between physical activity and grades is positive and significant (P < 0.01) and findings are consistent with previous work and affirm the complexity of the relationship of health to academic achievement. [8] Pei-An Liao1, Hung-Hao Chang et al discussed Physical fitness and academic performance: empirical evidence from the National Administrative Senior High School Student Data in Taiwan. They used a dataset of 149 240 university-bound senior high school students from 2009 to 2011 was constructed by merging two nationwide administrative datasets of physical fitness test performance and the university entrance exam scores.…”
Section: Literature Review:-mentioning
confidence: 99%
“…Nesta faixa etária, o crescimento ocorre mais lentamente e de forma constante, quando comparado aos adolescentes (SIGFÚSDÓTTIR et al, 2007;CECANE-SC, 2012;CRESSWELL et al, 2013).…”
Section: Introductionunclassified
“…Nesta fase, o rendimento escolar está diretamente relacionado com sua alimentação, pois carências nutricionais (ex.anemia ferropriva) ou desnutrição energético-proteica podem reduzir a capacidade de concentração, comprometendo o desenvolvimento e a aprendizagem da criança (SIGFÚSDÓTTIR et al, 2007;CECANE-SC, 2012). …”
Section: Introductionunclassified